Energy management in connected and disconnected mode of a photovoltaic system with a battery storage using an artificial neural network technique - Ezzitouni Jarmouni; Ahmed Mouhsen; Mohammed Lamhammedi; Zakarya Benizza (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
In order to reduce the inconvenience resulting from the use of the traditional energy sources (oil, gas and coal), the integration of renewable energy sources is among the better solutions. With the integration of green energy sources, there are several strategies that can be adopted, including the combination of clean energy sources (solar, wind, and biomass) with each other, or the combination of renewable sources with conventional sources. In this article, we focus on a photovoltaic system allowing the storage of energy in a battery with a coupling to the electrical grid. In order to overcome the problems related to the random operation that accompanies the use of photovoltaic systems, we have developed a control technique based on the use of artificial neural network technology. The complete system was designed and simulated on MATLAB Simulink.